Co-designing innovative cropping systems that match biophysical and socio-economic diversity: The DATE approach to Conservation Agriculture in Madagascar, Lao PDR and Cambodia. Issue 5 (7th October 2015) - Husson, Olivier; Tran Quoc, Hoá; Boulakia, Stéphane; Chabanne, André; Tivet, Florent; Bouzinac, Serge; Lienhard, Pascal; Michellon, Roger; Chabierski, Stéphane; Boyer, Johnny; Enjalric, Frank; Rakotondramanana,; et al.
Abstract: Rapid changes in agricultural systems call for profound changes in agricultural research and extension practices. The Diagnosis, Design, Assessment, Training and Extension (DATE) approach was developed and applied to co-design Conservation Agriculture-based cropping systems in contrasted situations. DATE is a multi-scale, multi-stakeholder participatory approach that integrates scientific and local knowledge. It emerged in response to questions raised by and issues encountered in the design of innovative systems. A key feature of this approach is the high input of innovative systems which are often although not exclusively based on conservation agricultural practices. Prototyping of innovative cropping systems (ICSs) largely relies on a conceptual model of soil–plant–macrofauna–microorganism system functioning. By comparing the implementation of the DATE approach and conservation agriculture-based cropping systems in Madagascar, Lao PDR, and Cambodia, we show that: (i) the DATE approach is flexible enough to be adapted to local conditions; (ii) market conditions need to be taken into account in designing agricultural development scenarios; and (iii) the learning process during the transition to conservation agriculture requires time. The DATE approach not only enables the co-design of ICSs with farmers, but also incorporates training and extension dimensions. It feeds back practitioners' questions to researchers, and provides a renewed and extended source of innovation to farmers.